Evolutionary Stability of Reputation-Based Incentive Mechanisms in P2P Systems - Goswami A.; Parashari G.S.; Gupta R. (My University, 2025)
Free riding is a severe problem in P2P systems. Although many incentive mechanisms based on reputation have been proposed to mitigate problem of free riding, reputation management fails to evolve as an evolutionary stable strategy (ESS) due to cost involved in keeping track of reputation. We prove that a system setting with one time entry fee, imposed on new comers and distributed among the peers that calculate reputation, makes reputation-based resource allocation an ESS. Then, we simulate the system model using evolutionary dynamics for its performance evaluation. © 2018 IEEE.